Advances in biblical Hebrew linguistics data, methods, and analyses - Moshavi, Adina Mosak; Notarius, Tania 1967-; World Congress of Jewish Studies 2013 Jerusalem (Winona Lake, Indiana Eisenbrauns, 2017)
"1. The verbless clause in biblical Hebrew: linguistic approaches / edited by Cynthia L. Miller -- 2. Phonology and morphology of biblical Hebrew: anintroduction / by Joshua Blau -- 3. A manual of Ugaritic / by Pierre Bordreuil and Dennis Pardee -- 4. Word order in the biblical Hebrew finite clause: a syntactic and pragmatic analysis of preposing / by Adina Moshavi -- 5. Oath formulas in biblical Hebrew / by Blane Conklin -- 6. Biblical Hebrew grammar visualized / by Francis I. Andersen and A. Dean Forbes -- 7. Time and the biblical Hebrew verb: the expression of tense, aspect, and modality in biblical Hebrew / by John A. Cook -- 8. Diachrony in biblical Hebrew / edited by Cynthia L. Miller-Naude and Ziony Zevit -- 9. The syntax of volitives in biblical Hebrew and Amarna Canaanite prose / by Helene Dallaire -- 10. The relative clause in biblical Hebrew / by Robert D. Holmstedt --11. Language change in the wake of empire: Syriac in Its Greco-Roman context / by Aaron Michael Butts -- 12. Advances in biblical Hebrew linguistics: data, methods, and analyses / edited by Adina Moshavi and Tania Notarius
"In recent decades, the study of biblical Hebrew has profited enormously from the application of methodologies derived from general linguistics. During the 16th World Congress of Jewish Studies, Adina Moshavi and Tania Notarius organized sessions devoted to exploring new developments in biblical Hebrew linguistics, bringing together many of the world's experts in the field. The papers in this volume are based on research presented at those sessions, along with additional articles specifically written for this volume. The essays included here address topics in philology, language contact, text-linguistics and linguistic pragmatics, syntax, and applied linguistics. The collection showcases biblical Hebrew linguistics as a dynamic and innovative endeavor that is making important contributions to the study of the Bible, Hebrew language, and modern linguistics"--
Includes bibliographical references and index
Based on papers presented at the 16th World Congress of Jewish Studies. - Includes bibliographical references and indexes
Einzelne Textstellen in hebräischer Schrift und Sprache
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Hebrew language -- Grammar; Hebrew language -- Grammar; Konferenzschrift; Konferenzschrift -- 28.07.2013-13.08.2013 -- Jerusalem